2021
DOI: 10.1111/jop.13177
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the impact of systemic sclerosis on oral health‐related quality of life in a UK population

Abstract: Background The objective of the present study was to identify the impact of systemic sclerosis (SSc) upon oral health‐related quality of life (OHRQoL) of affected individuals resident in the UK. Methods A total of 100 patients and their partners or carers were invited to complete questionnaires regarding the impact of SSc on quality of life and psychological well‐being using valid and reliable patient‐reported outcome measures (OHIP‐14, MHISS, OIDP, MDAS and HADS). A total of 50 patients with SSc and 18 partne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…Two cross-sectional studies found that oral health-related quality of life (OHQOL) was significantly worse in people with scleroderma compared with controls. 8,20 This finding was also reported in two narrative reviews 3,17 and one systematic literature review. 4 Furthermore, low OHQOL was significantly associated with low global quality of life in two cross-sectional studies 2,24 and in three literature reviews.…”
Section: Resultssupporting
confidence: 73%
See 4 more Smart Citations
“…Two cross-sectional studies found that oral health-related quality of life (OHQOL) was significantly worse in people with scleroderma compared with controls. 8,20 This finding was also reported in two narrative reviews 3,17 and one systematic literature review. 4 Furthermore, low OHQOL was significantly associated with low global quality of life in two cross-sectional studies 2,24 and in three literature reviews.…”
Section: Resultssupporting
confidence: 73%
“…Beaty et al’s 2 findings provide support for the results of Amin et al’s 22 research which demonstrated that ‘noticeability’ and ‘severity’ of facial differences had a significantly negative effect on self-esteem and anxiety. Similarly, Abdouh et al 8 revealed that 50% of participants with scleroderma reported difficulties in smiling without embarrassment, in comparison to just 6% of participants without scleroderma.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations